Pay, security, support and intention to quit relationship among academics in developing economy - Joarder, Mohd Hasanur Raihan; Subhan, Muhammad; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (LLC “СPС “Business Perspectives”, 2015)
This paper has examined the relationship between human resource management practices and intention to quit among the academics of private universities in Bangladesh. Out of 360 survey questionnaires which were distributed, 160 useable questionnaires included in the final analysis yielding at 44% response rate for the study. The results showed that pay and supports were significant and negatively related to faculty intention to quit behavior in any condition. However, the relationship of job security and faculty intention to quit depends on control variables used in this study.Therefore, this paper recommends that private university management especially in Bangladesh should pay more attention to these two practices in order to retain as well as to attract potential academics in the future. At the end, this paper highlights some limitations and suggestions for future research.